Feeding habits of four-finger threadfin fish, Eleutheronema tetradactylum, and its diet interaction with co-existing fish species in the coastal waters of Thailand - Iqbal, Teuku Haris; Hajisamae, Sukree; Lim, Apiradee; Jantarat, Sitthisak; Wang, Wen-Xiong; Tsim, Karl W.K. (PeerJ, 2023)
This study assessed the feeding habits of four-finger threadfin fish, Eleutheronema tetradactylum, and its diet relationship with other fish species in the tropics. Fish samples were collected from four locations along the coastal regions of Thailand. A whole year field sampling event was conducted to investigate the diet relationship of threadfin fish with other ten co-existing fish species in Pattani Bay during January 2021 and January 2022. E. tetradactylum was an active and specific predator with significant diet shift during ontogeny. Specifically, the juvenile fish fed largely on zooplankton especially Acetes/shrimp postlarvae, and small sized-fish fed on penaeid shrimps, while medium and large-sized fish shifted their diets to a combination of penaeid shrimp, fish and squid. Size and sex of fish as well as site of collection significantly affected gut fullness index and average number of food type (p < 0.05). Transitional sex fish predated almost entirely on other fishes (87.2%), whereas male and female fish fed mainly on penaeid shrimp (66.5%) and other fish (51.3%), respectively. Fish size and mouth opening controlled the size of prey, with the larger fish with larger mouth-opening fed primarily on the larger size of prey. Moreover, E. tetradactylum shared its diets inclusively with Epinephelus coioides, Johnius belangerii, Scomberomorus commerson, Scomberoides lysan, Otolithes ruber and Lutjanus russelli. Penaeid shrimp and teleost fish were the main food types shared by these fishes. This study provided important information on the feeding habits of E. tetradactylum and its diet relationship with other co-existing fish species living in the same habitat of a tropical coastal region.
Keywords: Feeding ecology; Stomach content; Fish behavior; Tropical fish; Fish ecology; Trophic organization